2023
DOI: 10.1111/add.16333
|View full text |Cite
|
Sign up to set email alerts
|

Craving modulates attentional bias towards alcohol in severe alcohol use disorder: An eye‐tracking study

Zoé Bollen,
Arthur Pabst,
Nicolas Masson
et al.

Abstract: Background and aimsCompeting models disagree on three theoretical questions regarding alcohol‐related attentional bias (AB), a key process in severe alcohol use disorder (SAUD): (1) is AB more of a trait (fixed, associated with alcohol use severity) or state (fluid, associated with momentary craving states) characteristic of SAUD; (2) does AB purely reflect the over‐activation of the reflexive/reward system or is it also influenced by the activity of the reflective/control system and (3) does AB rely upon earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In the authors' opinion, this is strongly related to the therapeutic approach of AUD, considering that AB training programs should be delivered to patients who display an approach AB for alcohol cues. A more recent study highlights that patients with severe AUD who experience significant levels of alcohol craving invested more time/interest in alcohol cues, while patients without alcohol craving showed an avoidance AB pattern [51]. These studies represent an indication that the treatment approach of AUD (e.g., AB training) should be personalized according to each individual and depending on the craving levels and the presence of an approach-related AB towards alcohol stimuli.…”
Section: Discussionmentioning
confidence: 97%
“…In the authors' opinion, this is strongly related to the therapeutic approach of AUD, considering that AB training programs should be delivered to patients who display an approach AB for alcohol cues. A more recent study highlights that patients with severe AUD who experience significant levels of alcohol craving invested more time/interest in alcohol cues, while patients without alcohol craving showed an avoidance AB pattern [51]. These studies represent an indication that the treatment approach of AUD (e.g., AB training) should be personalized according to each individual and depending on the craving levels and the presence of an approach-related AB towards alcohol stimuli.…”
Section: Discussionmentioning
confidence: 97%
“…CPD or Fagerström Test for Cigarette Dependence scores at 1 day and 8 weeks posttraining, and abstinence at 8 weeks, were not significantly associated with gaze dwell time proportions to smoking cues. Given that some studies found that craving to smoke (Mogg et al, 2003) and drink alcohol (Bollen et al, 2020(Bollen et al, , 2024 was positively associated with gaze dwell times to drug-related cues, we also examined the relationship between the Wisconsin Smoking Withdrawal Scale Craving scale and gaze dwell time proportions to smoking cues at baseline, 1 day post-ABM training, and 8 weeks post-ABM training, but found no significant associations. In terms of baseline characteristics associated with gaze dwell time proportions, analyses indicated that younger and more dependent smokers, as indicated by higher Fagerström Test for Cigarette Dependence scores, looked longer at the smoking than neutral cues.…”
Section: Discussionmentioning
confidence: 99%
“…Attentional bias is evident in anxiety disorders, depression, and addiction (Field et al, 2016;Suslow et al, 2020;Thomas et al, 2013;Wieser & Keil, 2020). This bias is particularly evident in craving, where individuals focus on stimuli resembling their substance use process (Bollen et al, 2024;Nejati et al, 2011). Craving is a central phenomenon in substance abuse and relapse, with signi cant implications for treatment (Culbertson et Various treatments, such as cognitive behavioral therapy (CBT), third-wave therapies, and psychoanalytical therapies, are available for managing anxiety, depression, and psychological issues in SUDs.…”
Section: Introductionmentioning
confidence: 99%